Synthesis and self-assembly of amphiphilic and biocompatible poly(vinyl alcohol)-block-poly(l-lactide) copolymer. (25th September 2016) - Mishra, Avnish Kumar; Park, Jicheol; Joseph, K.L. Vincent; Maiti, Sandip; Kwak, Jongheon; Choi, Chungryong; Hyun, Seung; Kim, Jin Kon
Abstract: Well-defined amphiphilic and biocompatible poly(vinyl alcohol)- block -poly(l -lactide) copolymers (PVA- b -PLLA) were synthesized by the combination of reversible addition-fragmentation chain transfer (RAFT), ring opening polymerization (ROP), and click chemistry. First, an innovative azide-functionalized xanthate mediated chain transfer agent (CTA) [S-(3-azidopropyl propanamide)-( O -butyl xanthate)] was synthesized and used for vinyl acetate (VAc) polymerization through RAFT. Then, azide-terminated poly(vinyl acetate) (azide-PVAc) was converted to the corresponding azide-terminated poly(vinyl alcohol) (azide-PVA) through hydrolysis. Alkyne-terminated poly (l -lactide) (alkyne-PLLA) was synthesized via ROP using a bifunctional initiator, having an alkyne and a hydroxyl group. Finally, azide-PVA and alkyne-PLLA were coupled by 1, 3 cycloaddition click reaction to get PVA- b -PLLA. Synthesized azide-PVAc, azide-PVA, alkyne-PLLA and PVA- b -PLLA were characterized by size exclusion chromatography and 1 H NMR spectroscopy. The self-assembly of PVA- b -PLLA in water was investigated by transmission electron microscope, atomic force microscopy, dynamic light scattering and 1 H NMR spectroscopy. Spherical micelles in water were clearly observed. The critical micelle concentration of PVA- b -PLLA in water was determined by fluorescence spectroscopy, and it was decreased with increasing the molecular weight of PLLA block. PVA- b -PLLA exhibited low cytotoxicity which could be used in biomedical application. Graphical abstract: Highlights: Azide-functionalized xanthate mediated chain transfer agent [S-(3-azidopropyl propanamide)-( O -butyl xanthate)]. Synthesis of azide terminated polyvinyl alcohol with less than PDI of 1.25. Well-defined amphiphilic and biocompatible poly(vinyl alcohol)- block -poly(l -lactide) copolymers. Self-assembly of PVA- b -PLLA in water is investigated.